Biomass production and bromatologic of silage to aerial parts of twenty accesses of sweet potato - Neumann, Mikael; Figueira, Danbia Nogueira [UNESP]; Heker Junior, Julio Cezar; Pinheiro Camargo, Leticia Kurchaidt; Vilela de Resende, Juliano Tadeu (Univ Estadual Centro-oeste, 2015)
The objective of this study was to evaluate the adaptability of 20 accesses of sweet potato as the characteristics of biomass production and physical composition of the plant, as well as the qualitative characteristics of the resulting silage: UGA001; UGA006; UGA019; UGA023; UGA030; UGA043; UGA045; UGA049; UGA056; UGA064; UGA066; UGA073; UGA077; UGA079; UGA082; UGA084; UGA087; UGA090; UGA095; UGA100 aiming for feeding ruminants. The experimental design was a randomized complete for 20 hits and four replicates, each replicate was represented by a plot with an area of 2 m(2). The UGA006 access excelled in the production of green and dry biomass with values of 127,267 kg ha(-1) and 15,345 kg ha(-1), respectively. The qualitative characteristics of different accessions of sweet potato relating to crude protein, neutral detergent fiber and acid detergent fiber were presented, in general, suitable for silage, but the dry matter proved inadequate the conservation process in this way, the high potential of wastewater generation.
Keywords: acid detergent fiber; crude protein; neutral detergent fiber; production of biomass